Financial disintermediation and the measurement of efficiency in banking: the case of Portuguese banks. (8th October 2008) - Lima, Filipa; Soares de Pinho, Paulo
In this paper we assess the impact of financial disintermediation on bank efficiency, with a focus on securitisation and bank-managed funds. For that purpose we use Banco de Portugal's proprietary database, which combines both accounting and statistical data for each single bank operating in Portugal. For both costs and profits, we simultaneously estimate frontiers and inefficiency determinants equations. We conclude that the usual practice found in the literature of not including off-balance sheet outputs in the frontier specification leads to a significant overestimation of bank inefficiency scores. While for cost efficiency, on- and off-balance sheet assets (and similarly for liabilities) do not seem to have a differentiated impact on efficiency, for profits we find that on- and off-balance sheet outputs have different efficiency impacts. Thus, we conclude that these assets and liabilities play an important role in the frontier specification. For the particular case of this data set, a discussion on efficiency determinants is also presented.